Endoscopic injection sclerotherapy for treating recurrent bleeding of small bowel angioectasias - Jing Yang; Lei Zhou; Dan Xu; Yan Fan; Heng Zhang (BMC Gastroenterology, 2023)
Abstract Background There is still no consensus on the preferred endoscopic therapy for small bowel angioectasias (SBAs). The aim of this study was to evaluate effectiveness and safety of endoscopic injection sclerotherapy (EIS) for treating recurrent bleeding of SBAs. Methods Sixty-six adult patients diagnosed with SBAs by capsule endoscopy (CE) or double-balloon enterscopy (DBE) examinations were enrolled in this retrospective study from September 2013 to September 2021. The patients were divided into an EIS group (35 cases) and a control group (31 cases) according to whether they underwent EIS treatment. Clinical characteristics, medical histories, lesion characteristics, main laboratory indicators, treatments, and outcomes were collected. The rates of re-bleeding, re-admission, and red blood cell (RBC) transfusion were compared between different groups after discharge. The rates of hospitalization and RBC transfusion were compared between before admission and after discharge in both groups. Odds ratios (ORs) and 95% confidence intervals (CIs) were used in the multivariate logistic regression analysis to assess relative factors for re-bleeding. Results All the rates of re-bleeding, re-admission and RBC transfusion after discharge in the EIS group were significantly lower than those in the control group (all P < 0.05). The rates of hospitalization and RBC transfusion after discharge were significantly lower than those before admission in the EIS group (both P < 0.05), while those did not reach significant differences in the control group (both P > 0.05). Multivariate logistic regression analysis showed that RBC transfusion before admission (OR, 5.655; 95% CI, 1.007–31.758, P = 0.049) and multiple lesions (≥ 3) (OR, 17.672; 95% CI, 2.246–139.060, P = 0.006) were significant risk factors of re-bleeding, while EIS treatment (OR, 0.037; 95% CI, 0.005–0.260, P < 0.001) was a significant protective factor. No endoscopic adverse events were observed during hospitalization and none of the enrolled patients died within 12 months after discharge. Conclusion EIS treatment had good effectiveness and safety for treating recurrent bleeding of SBAs, which could be considered as one of the first-line endoscopic treatment options for SBAs.